Consumption and Preferences of Dairy Products by Taiwanese and Polish Students - Katarzyna Świąder; Renata Banach; Fa-Jui Tan (Biology and Life Sciences Forum, 2021)
The consumption of dairy products, especially fermented milk products, to which are attributed many health-promoting properties, seems to be different on the Polish and Taiwanese markets. The aim of the study is to assess consumption and preferences concerning the choice of dairy products by Polish and Taiwanese consumers. The present study was conducted in Taichung, Taiwan, and in Warsaw, Poland. Data were obtained through the PAPI questionnaire, involving 200 respondents aged 19–25 years old. One hundred respondents were students from Department of Animal Science, National Chung Hsing University, and another one hundred were students from Department of Human Nutrition, Warsaw University of Life Sciences. The results obtained indicate that Poles (39%) were more likely to declare consuming dairy products daily compared to Taiwanese consumers (14%). Among the most frequently consumed dairy products, Polish students mentioned milk (89%), yoghurt (80%) and ripened cheese (69% of respondents). Taiwanese consumers, on the other hand, mentioned milk (95%), yoghurt, especially drinking yoghurt (81%), as well as dairy desserts (70%) and Yakult (69%). Polish students preferred regular fat yoghurt (53%) and low-fat yoghurt (22%), while the preferences of Taiwanese students were quite different, with most people declaring a preference for fat yoghurt (57%) and regular fat yoghurt (22%). The evaluation of dairy product, especially fermented milk products, consumption among consumers showed differences in consumption and preferences of these products between Polish and Taiwanese students.